LITERATURE REVIEW: ANALISIS WACANA KRITIS PADA SURAT KABAR TRIBUN LAMPUNG - Kuryanti, Tri; Hasanah, Uswatun (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2024)
This review article aims to discuss critical discourse analysis in newspapers. Critical discourse analysis is used to better understand the content of discourse by considering various aspects of both social and cultural phenomena. The method used in this review is a systematic approach to searching for data sources of articles, i. e. using the help of Publisher or Destroyer Software through several criteria. Data analysis is performed in several stages, namely reading the data sources of the found articles, identifying the data sources that match the review topics, creating a summary of each literature, then creating a summary of each article. Discussions on critical discourse analysis in newspapers have been conducted, one of them in a journal article entitled